Characterisation of microstructure and mechanical properties of cermets at micro- and nanoscales - Hussainova, I.; Antonov, M.; Jasiuk, I.; Du, X.
High resolution measurements of mechanical properties of the constituent phases of multi-phase materials are of immerse importance in design of new composites. In this study, the nanoindentation, X-ray analysis and microstructural SEM investigations have been used to reveal the properties and structural features of ceramic - metal composites involving chromium carbide based cermets with different additives (Mo and Cu)in nickel binder. The additives influence microstructural parameters such as grain size and residual stresses; however, nanohardness and Young's moduli of constituent phases remain less affected. Phase - specific mechanical properties are measured and correlated with bulk behaviour. Furthermore, hardness of the binder metal is found to be higher in cermet as compared to the bulk hardness of metal.
Keywords: CERMETS; MICROSTRUCTURE; NANOINDENTATION; HARDNESS; MODULUS OF ELASTICITY